Biochemical, Metabolomic, and Genetic Analyses of Dephospho Coenzyme A Kinase Involved in Coenzyme A Biosynthesis in the Human Enteric Parasite Entamoeba histolytica - Nurkanto, Arif; Jeelani, Ghulam; Yamamoto, Takehiro; Hishiki, Takako; Naito, Yoshiko; Suematsu, Makoto; Hashimoto, Tetsuo; Nozaki, Tomoyoshi (Frontiers in Microbiology, 2018)
Coenzyme A (CoA) is an essential cofactor for numerous cellular reactions in all living organisms. In the protozoan parasite Entamoeba histolytica, CoA is synthesized in a pathway consisting of four enzymes with dephospho-CoA kinase (DPCK) catalyzing the last step. However, the metabolic and physiological roles of E. histolytica DPCK remain elusive. In this study, we took biochemical, reverse genetic, and metabolomic approaches to elucidate role of DPCK in E. histolytica. The E. histolytica genome encodes two DPCK isotypes (EhDPCK1 and EhDPCK2). Epigenetic gene silencing of Ehdpck1 and Ehdpck2 caused significant reduction of DPCK activity, intracellular CoA concentrations, and also led to growth retardation in vitro, suggesting importance of DPCK for CoA synthesis and proliferation. Furthermore, metabolomic analysis showed that suppression of Ehdpck gene expression also caused decrease in the level of acetyl-CoA, and metabolites involved in amino acid, glycogen, hexosamine, nucleic acid metabolisms, chitin and polyamine biosynthesis. The kinetic properties of E. histolytica and human DPCK showed remarkable differences; e.g., the Km values of E. histolytica and human DPCK were 58-114 μM and 5.2 μM toward dephospho-CoA and 15-20 μM and 192 μM for ATP, respectively. Phylogenetic analysis also supported the uniqueness of the amebic enzyme compared to the human counterpart. These biochemical, evolutionary features, and physiological importance of EhDPCKs indicate that EhDPCK represents the rational target for the development of anti-amebic agents.